2022
DOI: 10.3389/fneur.2022.827780
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar and Prefrontal Structures Associated With Executive Functioning in Pediatric Patients With Congenital Heart Defects

Abstract: ObjectiveChildren, adolescents, and young adults with congenital heart defects (CHD) often display executive dysfunction. We consider the prefrontal and cerebellar brain structures as mechanisms for executive dysfunction among those with CHD.Methods55 participants with CHD (M age = 13.93) and 95 healthy controls (M age = 13.13) completed magnetic resonance imaging (MRI) of the brain, from which we extracted volumetric data on prefrontal and cerebellar regions. Participants also completed neuropsychological tes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Animal research evidence indicated that hemi-cerebellectomized animals are unable to flexibly switch to a new set of rules, despite having intact motor responses (De Bartolo et al 2009; Dickson et al 2017). A few small-sample human studies (Ben-Soussan et al 2015; Kansal et al 2017; Badaly et al 2022; Kühn et al 2012; Paradiso et al 1997; Parker et al 2008; Koppelmans et al 2017; Bauer et al 2009; Bernard and Seidler 2013) have underlined a cerebellar role in mediating cognitive flexibility. The cerebellar correspondence of cognitive flexibility fits well with evidence from cerebellar lesions (Stoodley and Schmahmann 2010; Argyropoulos et al 2020; Stoodley et al 2016) and theoretical accounts of cognitive dysmetria theory (Andreasen, Paradiso, and O’Leary 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Animal research evidence indicated that hemi-cerebellectomized animals are unable to flexibly switch to a new set of rules, despite having intact motor responses (De Bartolo et al 2009; Dickson et al 2017). A few small-sample human studies (Ben-Soussan et al 2015; Kansal et al 2017; Badaly et al 2022; Kühn et al 2012; Paradiso et al 1997; Parker et al 2008; Koppelmans et al 2017; Bauer et al 2009; Bernard and Seidler 2013) have underlined a cerebellar role in mediating cognitive flexibility. The cerebellar correspondence of cognitive flexibility fits well with evidence from cerebellar lesions (Stoodley and Schmahmann 2010; Argyropoulos et al 2020; Stoodley et al 2016) and theoretical accounts of cognitive dysmetria theory (Andreasen, Paradiso, and O’Leary 1998).…”
Section: Discussionmentioning
confidence: 99%
“…While prior studies indicate structural brain network reorganization, our findings suggest that the global functional network remains largely undifferentiated, with predominantly regional differences. Regional, rather than global differences, may explain higher variance observed in CHD patient scores, but still within normal limits on tests of intelligence (Badaly et al, 2022; Wallace et al, 2023)…”
Section: Discussionmentioning
confidence: 97%
“…al found that preterm infants with exposure to morphine in the neonatal period had decreased cerebellar volumes and worse neurodevelopmental outcomes. 79 Additionally, our group has previously shown that CHD children with reduced cerebellar volumes scored worse in tests for working memory, inhibitory control, and mental flexibility 80 . We also demonstrated that the superior surface of the cerebellum, primarily composed of the posterior lobe and the midline vermis, is an area particularly susceptible to alterations in morphology, indicating possible regions specifically affected by dysmaturation in CHD.…”
Section: Discussionmentioning
confidence: 98%